A closer look at the elephant in the room: the distinctiveness of geographical indications. Issue 1 (February 2021) - Song, Xinzhe
Abstract : The term 'distinctiveness' is used in trademark law to refer to the capacity of a trademark to distinguish the goods of one undertaking from those of other undertakings. The importance of this concept can be seen in Article 15 of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement), which provides that any sign having distinctiveness shall be capable of constituting a trademark. Gradually, 'distinctiveness' has come to be used to describe the distinguishing capacity of other distinctive signs, including geographical indications (GIs). This article explores the distinctiveness of GIs. It begins with a discussion of the meaning of GI distinctiveness in the different GI protection contexts to reveal its particularity compared to the traditional concept of trademark distinctiveness. The second part of the discussion shows, however, that the concept of GI distinctiveness is not given sufficient importance in the protection of GIs, and is confused with the distinctiveness of collective or certification marks. This article therefore calls for an approach that recognizes the importance and the particularity of the distinctiveness of GIs in the design of GI protection mechanisms.